2019
DOI: 10.1111/febs.14760
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into enzymatic catalysis by trehalase from the insect gut endosymbiont Enterobacter cloacae

Abstract: Energy metabolism in the diamondback moth Plutella xylostella is facilitated by trehalase, an enzyme which assists in trehalose hydrolysis, from the predominant gut bacterium Enterobacter cloacae. We report the biochemical and structural characterization of recombinant trehalase from E. cloacae (Px_EclTre). Px_EclTre showed KM of 1.47 (±0.05) mm, kcat of 6254.72 min−1 and Vmax 0.2 (±0.002) mm·min−1 at 55 °C and acidic pH. Crystal structures of Px_EclTre were determined in the ligand‐free form and bound to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Furthermore, the concentration of some important nutritional indices, containing hemolymph protein, glucose, triglyceride, and trehalose which can indicate the nutrition and metabolic status of animal host well (Ridley et al, 2012; Newell and Douglas, 2014), were measured to reveal the physiological consequences of gut microbiota on their host phenotype. It has been verified that Enterobacter cloacae can produce various glycolytic enzymes, containing cellulases, trehalases and other glucosidases, which participate in food digestion (Xia et al, 2017; Adhav et al, 2019). Moreover, Lactococcus lactis is a lactic acid bacterium which is involved in digesting and fermenting some plant polymers to improve insect nutrition acquisition (Passerini et al, 2013; Zhou H. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the concentration of some important nutritional indices, containing hemolymph protein, glucose, triglyceride, and trehalose which can indicate the nutrition and metabolic status of animal host well (Ridley et al, 2012; Newell and Douglas, 2014), were measured to reveal the physiological consequences of gut microbiota on their host phenotype. It has been verified that Enterobacter cloacae can produce various glycolytic enzymes, containing cellulases, trehalases and other glucosidases, which participate in food digestion (Xia et al, 2017; Adhav et al, 2019). Moreover, Lactococcus lactis is a lactic acid bacterium which is involved in digesting and fermenting some plant polymers to improve insect nutrition acquisition (Passerini et al, 2013; Zhou H. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All manipulations were performed with the molecular modelling program YASARA and the YASARA/WHATIF twinset and figures were created with PyMOL 2.0. The ligand free and inhibitor bound crystal structures of trehalase from Enterobacter cloacae (GH37 family) (PDB code 5Z6H and 5Z66, respectively) 33 were used as template for docking. Trehalose derivative structures were created with YASARA Structure and subsequently minimised with the AMBER03 force field.…”
Section: Molecular Modellingmentioning
confidence: 99%
“…Unfortunately, no structural elucidation was possible for the enzyme from M. smegmatis as no crystal structure of a trehalase from family GH15 has yet been determined. However, several crystal structures of trehalases from family GH37 are described in literature, namely from Escherichia coli, Saccharomyces cerevisiae and Enterobacter cloacae 33,[35][36][37] . Interestingly, the latter has been crystallised in two different forms, i.e.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, it is a major haemolymph sugar, serving as a prime source of energy for flight and tolerance to stress (Becker, Schlöder, Steele, & Wegener, ). The elucidation of trehalose metabolism has been one of the most exciting developments in our understanding of insect metabolism in recent years (Adhav et al, ; Cornette et al, ). A number of studies have demonstrated a correlation between intracellular trehalose levels and the ability of insects to survive various environmental stresses, such as starvation, osmotic and oxidative stresses, and extremes in temperature (Benoit, Lopez‐Martinez, Elnitsky, Lee, & Denlinger, ; Cornette et al, ; Juliano, O'Meara, Morrill, & Cutwa, ).…”
Section: Introductionmentioning
confidence: 99%